The end of the American century - Schlossstein, Steven (Congdon & Weed, 1989)
This is a well-written, engaging, and impressive work in scope and integration. The End of the American Century provides the information and analysis for the informed discussion and debate about our economic and political problems that must take place as we face the monumental decisions that will decide our fate over the coming generations. It should be read by all who share a deep concern for the American future, but especially by young people who must live in it.